2004
DOI: 10.1007/s00441-004-0882-x
|View full text |Cite
|
Sign up to set email alerts
|

Odontoblasts induced from mesenchymal cells of murine dental papillae in three-dimensional cell culture

Abstract: In an organ culture system under a three-dimensional microenvironment that provides the conditions needed for odontoblast differentiation, a row of odontoblasts can be induced (Kikuchi et al. 1996, 2001). Therefore, in a newly designed three-dimensional cell culture system that fulfils the conditions necessary for odontoblast differentiation (Kikuchi et al. 2002), we examined whether dental papilla cells in rat mandibular incisors could differentiate into tubular dentine-forming cells. In our previously establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 74 publications
2
24
0
1
Order By: Relevance
“…When these stem cells at the 9 th passage are implanted into the renal capsules, most stem cells are in a differentiated state, which conversely leads to the decrease of stem cell number, results in the loss of balance between stem cell proliferation and differentiation, and finally brings about the irregular tissue development [19]. Since the difference between dentin and bone is largely due to the different arrangement of matrix [24], irregular array of dentin and bone matrix secreted by odontoblasts and osteoblasts respectively may bring about the same appearance of bone-like calcification. Finally, the cell number of differentiated chondrocytes may be too limited (weak expression of COL II protein/gene) to perform the sustainable morphogenesis of cartilage in DPSC-P9 group.…”
Section: Discussionmentioning
confidence: 99%
“…When these stem cells at the 9 th passage are implanted into the renal capsules, most stem cells are in a differentiated state, which conversely leads to the decrease of stem cell number, results in the loss of balance between stem cell proliferation and differentiation, and finally brings about the irregular tissue development [19]. Since the difference between dentin and bone is largely due to the different arrangement of matrix [24], irregular array of dentin and bone matrix secreted by odontoblasts and osteoblasts respectively may bring about the same appearance of bone-like calcification. Finally, the cell number of differentiated chondrocytes may be too limited (weak expression of COL II protein/gene) to perform the sustainable morphogenesis of cartilage in DPSC-P9 group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that MSC-like dental pulp stem cells (dental pulp-derived MSCs, DPSCs) exist in the dental pulp (16,25). One of the major roles of DPSCs is thought to be their ability to supply hard tissue components by differentiating into odontoblasts (10). BM-MSCs have also been suggested to supply hard tissue components by differentiation into osteoblasts (28).…”
Section: Introductionmentioning
confidence: 99%
“…Besides transgenic mouse studies, dental epithelium and mesenchyme derived cells cultured in vitro provide important strategies to study these signaling factors. Dental papilla cells derived from dental papilla and capable of odontoblast differentiation and dentin formation provide a useful model for studying the morphogenesis and differentiation of dental papilla ectomesenchyme during tooth development (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%